1997
DOI: 10.1021/bi963069l
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Mediated Signaling in Cholesterol-Enriched Arterial Smooth Muscle Cells. 1. Reduced Membrane-Associated G-Protein Content Due to Diminished Isoprenylation of G-γ Subunits and p21ras

Abstract: Mechanisms contributing to altered heterotrimeric G-protein expression and subsequent signaling events during cholesterol accretion have been unexplored. The influence of cholesterol enrichment on G-protein expression was examined in cultured smooth muscle cells that resemble human atherosclerotic cells by exposure to cationized LDL (cLDL). cLDL, which increases cellular free and esterified cholesterol 2-fold and 10-fold, respectively, reduced the cell membrane content of Gαi-1, Gαi-2, Gαi-3, Gq/11, and Gαs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…No one has studied the MAP kinase activity in caveolae of cholesterolenriched cells, but our results predict the enzyme would be hyporesponsive to growth factors such as EGF. Recently, Pomerantz et al (35) reported that cultured smooth muscle cells with elevated levels of cholesterol exhibit a reduced MAP kinase activity in response to platelet-derived growth factor. At the other extreme, transformed cells have below normal amounts of caveolae cholesterol, which is restored to normal after the cells are transfected with caveolin-1 (10).…”
Section: Discussionmentioning
confidence: 99%
“…No one has studied the MAP kinase activity in caveolae of cholesterolenriched cells, but our results predict the enzyme would be hyporesponsive to growth factors such as EGF. Recently, Pomerantz et al (35) reported that cultured smooth muscle cells with elevated levels of cholesterol exhibit a reduced MAP kinase activity in response to platelet-derived growth factor. At the other extreme, transformed cells have below normal amounts of caveolae cholesterol, which is restored to normal after the cells are transfected with caveolin-1 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane protein preparation for Ras and Rac analysis was similar to that described by Pomerantz et al (41). Briefly, VSMCs were washed with cold phosphate-buffered saline (4°C), scraped in phosphate-buffered saline, pelleted, and resuspended in 500 l of homogenizing buffer (25 mM Hepes, 1.0 mM EDTA, 1 g/ml leupeptin, 1 g/ml pepstatin A, and 100 M phenylmethylsulfonyl fluoride).…”
Section: Methodsmentioning
confidence: 99%
“…Armstead 31 has recently demonstrated that superoxide inhibits the dilation of cerebral vessels mediated by G PTX protein. Furthermore, Pomerantz et al 32 have shown that the G i␣ level of vascular smooth muscle cells is decreased under the condition of cholesterol enrichment by post-transcriptional mechanisms such as diminished isoprenylation of G ␤␥ subunits, which could lead to low anchoring of G i protein.…”
Section: Hypercholesterolemia-induced Impairment Of the Cross-talkmentioning
confidence: 99%